Gene cloning, sequencing, expression and biological activity of giant panda (Ailuropoda melanoleuca) interferon-α - Tan, Xue-Mei (Mol Immunol, 2007)
The giant panda (Ailuropoda melanoleuca) is an endangered species and indigenous to China. In mammals, multiple subtypes of interferon-α (IFN-α) exist, most of which possess antiviral activity. Little is known about giant panda IFN-α genes and the role they may play in giant panda immunological responses to viruses. We have cloned genes encoding 12 giant panda IFN-α (AmIFN-α or AmIFNA) subtypes that share from 90 to 99% amino acid sequence identity. AmIFN-α12 has one additional amino acid at position 57, which is not present in other subtypes. Sequence identity of the AmIFN-α proteins encoded by the 12 genes compared to human IFN-α2 is approximately 58%. Unlike most of the human subtypes, each of the 12 giant panda IFN sequences has an N-glycosylation recognition site. Expression of all 12 AmIFN-α subtypes in 293 cells was confirmed by SDS-PAGE and Western blotting analysis. The antiviral activity and antiproliferative activity of each AmIFN-α subtype produced in transiently transfected 293 cell cultures were tested in vitro. All AmIFN-α subtypes were found to be stable at pH 2 or 65 °C and to exhibit antiviral activity. Some IFN subtypes (AmIFN-α8 and AmIFN-α4) showed higher biological activity levels than others, whereas AmIFN-α11 exhibited lower activity. AmIFN-α had various antiproliferative activities to different target cells. To B16 cells, AmIFN-α3, AmIFN-α4, AmIFN-α8 had the highest activities, while to K562 cells, AmIFN-α3, AmIFN-α7, AmIFN-α10 had the highest activities. The various IFN-α subtypes displayed a good correlation between their antiviral and antiproliferative potencies.